2020
DOI: 10.1097/acm.0000000000002941
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Success of Medical School Applicants With Scores in the Middle Third of the MCAT Score Scale

Abstract: for their assistance with outreach to the deans. Enrollment data for DO-granting schools were provided by Erik Guercio of the American Association of Colleges of Osteopathic Medicine. The authors owe special thanks to the AAMC Communications team for their work on editing and design. The AAMC welcomes your comments and suggestions for future editions of this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…This group revealed that one quarter of the surveyed US‐mainland MD‐granting schools matriculated at least 20% of its incoming class with applicants with midrange MCAT scores, likely to reflect more mission‐based selection preferences. However, half of US‐mainland MD‐granting schools had 7.5% or fewer matriculants with midrange MCAT scores; one quarter of US‐mainland MD‐granting schools had 2% or fewer matriculants 12 . This is strong evidence that an applicant's chances of being interviewed and offered admission still relies on a high MCAT score—in addition to undergraduate GPA—as a critical admissions selection factor and likely predictor of success in preclinical medical education 13 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This group revealed that one quarter of the surveyed US‐mainland MD‐granting schools matriculated at least 20% of its incoming class with applicants with midrange MCAT scores, likely to reflect more mission‐based selection preferences. However, half of US‐mainland MD‐granting schools had 7.5% or fewer matriculants with midrange MCAT scores; one quarter of US‐mainland MD‐granting schools had 2% or fewer matriculants 12 . This is strong evidence that an applicant's chances of being interviewed and offered admission still relies on a high MCAT score—in addition to undergraduate GPA—as a critical admissions selection factor and likely predictor of success in preclinical medical education 13 .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study showed that medical school applicants whose MCAT scores fell in the middle of the composite score scale generally were more socioeconomically and racially/ethnically diverse compared to the high-MCAT-score applicant group. 12 This group revealed that one quarter of the surveyed US-mainland MD-granting schools matriculated at least 20% of its incoming class with applicants with midrange MCAT scores, likely to reflect more missionbased selection preferences. However, half of US-mainland MD-granting schools had 7.5% or fewer matriculants with midrange MCAT scores; one quarter of US-mainland MDgranting schools had 2% or fewer matriculants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This spring, Academic Medicine published a collection of articles summarizing the MVC's research so far. These articles describe how well MCAT scores predict students' performance in the first year of medical school, 17 how examinees prepare for and perform on the exam, 18 how admissions committees can admit more diverse classes by considering applicants with a wider range of MCAT scores, 19 how to help students strategically prepare for the exam, 20 and how structural racism and inequality affect educational opportunity academic achievement. 29 Visit aamc.org/mvc2020articles to read the articles.…”
Section: Content Categoriesmentioning
confidence: 99%